2010
DOI: 10.1038/cdd.2010.20
|View full text |Cite
|
Sign up to set email alerts
|

Activation of GPR30 inhibits the growth of prostate cancer cells through sustained activation of Erk1/2, c-jun/c-fos-dependent upregulation of p21, and induction of G2 cell-cycle arrest

Abstract: G protein–coupled receptor 30 (GPR30) exhibits estrogen-binding affinity and mediates nongenomic signaling of estrogen to regulate cell growth. We here demonstrated for the first time, in contrast to the reported promoting action of GPR30 on the growth of breast and ovarian cancer cells, that activation of GPR30 by the receptor-specific, non-estrogenic ligand G-1 inhibited growth of androgen-dependent and -independent prostate cancer (PCa) cells in vitro and PC-3 xenografts in vivo. However, G-1 elicited no gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
201
1
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(240 citation statements)
references
References 54 publications
23
201
1
2
Order By: Relevance
“…Previous studies have shown that the upregulation of GPR30 by EGF engages E2 to boost the proliferation of ERα-negative breast cancer cells and ERα-positive Ishikawa endometrial cancer cells (11,12). However, GPR30 has been shown to have a growth inhibitory effect on certain cell types (25)(26)(27)(28)(29). Our findings were consistent with those from other reports demonstrating that the activation of GPR30 signaling inhibits MCF-7 cell growth (26,29).…”
Section: Gpr30 Plays An Inhibitory Role In the Proliferative Effect Isupporting
confidence: 92%
“…Previous studies have shown that the upregulation of GPR30 by EGF engages E2 to boost the proliferation of ERα-negative breast cancer cells and ERα-positive Ishikawa endometrial cancer cells (11,12). However, GPR30 has been shown to have a growth inhibitory effect on certain cell types (25)(26)(27)(28)(29). Our findings were consistent with those from other reports demonstrating that the activation of GPR30 signaling inhibits MCF-7 cell growth (26,29).…”
Section: Gpr30 Plays An Inhibitory Role In the Proliferative Effect Isupporting
confidence: 92%
“…11 GPER has been suggested to be important in rapid, nonclassic, estrogen-induced growth regulation in some tissues. [12][13][14][15][16][17][18][19] GPER's growth-regulating effects have been extensively studied, 13,18,[20][21][22][23][24][25][26] primarily in reproductive tissues and in cancer cells. Notably, GPER activation has also been shown to attenuate adverse cardiac ventricular remodeling in mRen2 Lewis rats.…”
mentioning
confidence: 99%
“…Naturally, more research has been conducted in aggressive cell lines and primary tissues. In contrast to the effects of GPER activation in breast and ovarian cancers, where it promotes growth, it has been identified that the treatment of castration-resistant prostate cancer with a specific GPER agonist, G1, actually inhibits the growth of prostate cancer in PC-3, DU145 and LNCaP cell lines in vitro and in vivo PC3 xenografts (Chan et al 2010, Lam et al 2014. While most studies only reported tumour inhibition in castration-resistant cell lines, Lam and coworkers found that G1 treatment has no effect on androgen-sensitive LNCaP cells in vitro and in vivo xenograft mouse models, whereas it had a significant effect on castration-resistant tumours without apparent toxicity to the host (Lam et al 2014).…”
Section: :6mentioning
confidence: 99%
“…The mechanisms by which the GPER agonist G1 has anti-tumour effects has been explored in PC3 cell line in vitro and in vivo xenograft-castrated mice models and is reported to be via upregulation of p21 and consequent cell cycle arrest at G2 phase (Chan et al 2010). Although GPER activation inhibits growth of prostate cancer, it increases proliferation of other tissues including testicular germ cells and urothelial cells of the bladder and urinary tract (Chevalier et al 2011, Huang et al 2015.…”
Section: :6mentioning
confidence: 99%